(3GdCSWhd GdJLGQj GdHMQjs - (3Cjef(B, (3GdfMQGhjs ((3GdEScfOQjI(B:s (3eQcR GdEScfOQjI ddcJGH(B,s, 2008)
(3jVe JGQjN YQjb ddHMQjI GdYQHjI, GdJbSjeGJ GdeNJdaI dSaf GdCSGWjd GdHMQjI aj GdYGde, GdOhQ GdEbJUGOj ddCSWhd GdJLGQj GdHMQj GdEWGQ GdEbJUGOj ddESJKeGQ aj Saf GdCSWhd, efXheI EOGQI GdSdGeI GdOhdjI hCKQgG Ydi Saf GdCSWhd, GdeJWdHGJ hGdbhGYO GdOhdjI dYedjGJ GdSdGeI ddSaf hdefY GdJdhKs
Keywords: (3GdCSWhds; (3GdJLGQI GdHMQjIs; (3GdSaf GdJLGQjIs